353 A Direct-to-Patient Mailing about Sedative-Hypnotics and Online CBT-I: Participant Reported Use of Study Materials. (3rd May 2021) - Mak, Selene; Ulmer, Christi; Kaufman, Chritopher; Alessi, Cathy; Martin, Jennifer; Smith, Jason; Mitchell, Michael; Josephson, Karen; McCarthy, Michaela; Lum, Hillary; Fung, Constance
Abstract: Introduction: Cognitive behavioral therapy for insomnia (CBT-I) is recommended as first-line treatment for chronic insomnia disorder for all adults. Older adults are often prescribed sedative-hypnotics (e.g., benzodiazepine receptor agonists, BRAs) for insomnia, despite observational studies showing these medications increase risk of falls, fractures, and cognitive decline. In an ongoing randomized controlled trial, we are testing "Sleep EducatioN Information Sent Directly to Patients (SEND), " a novel program combining direct-to-patient mailing with information about access to an online CBT-I resource, compared to a similarly structured control condition. In the current study, we surveyed participants in both groups to examine their self-reported use of intervention or control materials. Methods: In the larger trial, 1, 672 Veteran participants (aged >=65 years, receiving care from a Colorado VA facility, and prescribed a BRA) were randomized to receive the SEND intervention brochure with information on how to access a free, anonymous online CBT-I resource (n=836) or control condition brochure with information about general sleep education (n=836). Six months after the initial brochure mailing, all participants were mailed a blinded survey querying participants' recollection and use of the mailed materials. We used chi-squared tests to compare survey responses for SEND versus control groups. Results: 354 surveys were returned by study participants (overall response rate: 21%; SEND: 172 [20%], control: 182 [22%]). Respondents were 94% male with mean age 71.7 years (no difference between groups). In the SEND group, 97 (56%) reported receiving the brochure, 18 (10%) visited the website, and 14 (8%) discussed the brochure with their provider. No significant differences between groups were observed in the number of participants who reported receiving the brochure (chi2=2.96, p=.085); visiting the website (chi2=0.0253, p=.874); or discussing the brochure with their provider (chi2=1.91, p=.167). Conclusion: At 6-months follow-up, over half of participants recalled receiving a mailing about sedative-hypnotics. A modest number reported visiting the online CBT-I program and a similar number discussed the materials with their healthcare provider. Similar results between groups suggest successful blinding of the intervention and control participants. If successful, the SEND intervention may provide a low-touch, low-cost approach to address BRA over-use in some older adults. Support (if any):